AFM Identification of Beetle Exocuticle: Bouligand Structure and Nanofiber Anisotropic Elastic Properties. (27th December 2016) - Yang, Ruiguo; Zaheri, Alireza; Gao, Wei; Hayashi, Cheryl; Espinosa, Horacio D.
Abstract : One of the common architectures in natural materials is the helicoidal (Bouligand) structure, where fiber layers twist around a helical screw. Despite the many studies that have shown the existence of Bouligand structures, methods for nanoscale structural characterization and identification of fiber mechanical properties remain to be developed. In this study, we used the exocuticle of Cotinis mutabilis (a beetle in the Cetoniinae) as a model material to develop a new experimental‐theoretical methodology that combines atomic force microscopy‐based nanoindentation and anisotropic contact mechanics analysis. Using such methodology, we studied both the helicoidal structure and the mechanical properties of its constituent fibers. The twist angle between the layers was found to be in the range of 12°–18° with a pitch size of 220 nm for the helicoidal pattern. In addition, the constituent fiber diameter was measured to be approximately 20 nm, which is consistent with the fiber diameters found in helicoids of other arthropod species. The longitudinal, transverse, and shear modulus of the nanofiber were determined to be 710 MPa, 70 MPa, and 90 MPa, respectively. The established experimental‐theoretical methodology promises to be a useful tool for nanoscale characterization of helicoidal and other structures found in biological materials. Abstract : Using beetle's exocuticle as a model system, an atomic force microscopy‐based experimental–theoretical methodology is developed to characterize its helicoidal fiber structure and identify anisotropic material properties of constituent nanofibers. The method is applicable to other biomaterial architectures.